Maximizing signless Laplacian or adjacency spectral radius of graphs subject to fixed connectivity - Ye, Miao-Lin; Fan, Yi-Zheng; Wang, Hai-Feng (Linear algebra and its applications, 2010)
In this paper, we characterize the graphs with maximum signless Laplacian or adjacency spectral radius among all graphs with fixed order and given vertex or edge connectivity. We also discuss the minimum signless Laplacian or adjacency spectral radius of graphs subject to fixed connectivity. Consequently we give an upper bound of signless Laplacian or adjacency spectral radius of graphs in terms of connectivity. In addition we confirm a conjecture of Aouchiche and Hansen involving adjacency spectral radius and connectivity.